PID Temperature Control on Blood Warmer Equipped with Patient Temperature and Blood Temperature - Santoso, Clarissa Grace; Hamzah, Torib; Syaifudin, Syaifudin; Mujahid, Muhammad Umer Farooq (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Blood, being a sensitive biological fluid, can undergo cellular and biochemical changes when subjected to temperatures that are too high or too low. Consequently, administering blood that is not at an appropriate temperature can result in hemolysis (the destruction of red blood cells), clotting issues, and even patient harm. Therefore, ensuring that the temperature of transfused blood remains within a specific range is crucial for the success and safety of the procedure, The objective of the described project is to enhance the success and safety of blood transfusion procedures by implementing a temperature control system using various sensors and control techniques. The methodology employed in this project, DS18B20 Sensor This sensor is used to measure the temperature of the blood being transfused. It provides accurate temperature readings, which are crucial for maintaining optimal conditions. MLX90614 Sensor, This sensor is utilized to adjust the temperature of the transfused blood according to the recipient's body temperature. It ensures that the introduced blood is compatible with the patient's internal environment. PID Control: The Proportional-Integral-Derivative control technique is implemented to regulate the heater that maintains the temperature of the blood. The PID parameters (Kp, Ki, Kd) are tuned to achieve precise control and response. Fuzzy Control: Fuzzy logic control is also employed for temperature regulation. While PID control is known for its rapid response and stability, Fuzzy control is utilized to handle potential non-linearities and complex relationships in the system. PID and Fuzzy control techniques are evaluated and compared in terms of their effectiveness in regulating blood temperature during transfusion.This study uses the DS18B20 Sensor to control the heater with PID and Fuzzy controls, the MLX90614 Sensor to adjust the temperature according to the patient's body temperature and the Optocoupler Sensor as an indicator when fluids run out.